Design principles of hybrid approaches in new product development: a systematic literature review - de Vasconcelos Gomes, Leonardo Augusto; Seixas Reis de Paula, Rafael Augusto; Figueiredo Facin, Ana Lúcia [UNESP]; Chagas Brasil, Vinicius; Sergio Salerno, Mario (My University, 2021)
Setting the right approach for new product development (NPD) in the presence of uncertainty remains an ongoing debate in innovation management. Stage-gate systems (SGS) and agile methodology (AM) are the dominant approaches. Recently, hybrid approaches (combining SGS and AM) have been proposed. Although these hybrid approaches represent a significant development in NPD, combining them without considering their design principles might lead to contradictory and competing conceptual formulations, thus increasing the difficulty of comparison among studies. Moreover, scholars and practitioners may struggle to understand when, why and how a certain configuration of the NPD process provides the right response to different manifestations of uncertainty. The current literature faces problems regarding the clarity of design principles (e.g. flexibility and adaptability), and this has led to research gaps concerning the uncertainty contingency and outcomes of hybrid approaches. This study combines bibliometric and content analyses to identify four design parameters and principles of NPD hybrid approaches: flexibility, adaptability, velocity and integration. Our findings might help advance the development and comparison of different hybrid approaches.